PERBANDINGAN UMUR SIMPAN BAHAN PAKAN TERNAK YANG DITAMBAHKAN PENGAWET ASAM PROPIONAT DENGAN MODEL PERSAMAAN ARRHENIUS - adisti, rizqa (Jurnal Peternakan Nusantara, 2021)
Estimating the shelf life of feed ingredients is very important to know in order to assist the feed industry in managing storage, availability and maintaining the nutritional quality of the animal feed produced. The purpose of this study was to compare pollard and wheat bran with added propionic acid preservative at different storage temperatures based on the peroxide value using the Arrhenius model. Shelf life was determined by adding propionic acid to pollard and wheat bran and then storing at 15, 35 and 45 °C for 49 days in an incubator. The parameter used in this research is the peroxide number. The results of this study are based on the calculation of the Arrhenius model. In pollard with propionic acid preservative, it is known that the shelf life at 15, 35 and 45 °C is 38.9 months, 35.6 months and 15.9 months, respectively, while pollard without preservatives is 27.3 months, 22.2 months and 13.1 months. In wheat bran with propionic acid preservative, it is known that the shelf life at 15, 35 and 45 °C is 32.9 months, 21.2 months and 21.2 months, while wheat bran without preservatives is 25.1 months, 15, respectively. 1 month and 14.8 months Keywords: Arrhenius, peroxide, pollard, propionic acid, wheat bran.